Development of Spontaneous Echocardiographic Contrast After Transarterial Occlusion of a Patent Ductus Arteriosus in an Adult Dog With Concurrent Pulmonary Hypertension - Winter, Randolph L.; Remaks, Julia D.; Newhard, Daniel K. (Frontiers in Veterinary Science, 2020)
An 8-year-old intact female Chihuahua was presented for evaluation and possible occlusion of a previously diagnosed patent ductus arteriosus (PDA). Transthoracic echocardiography revealed left ventricular and left atrial enlargement, enlargement of the main pulmonary artery, and a PDA with bidirectional shunting. Tricuspid regurgitant velocities suggested moderate pulmonary hypertension. The PDA was occluded with an Amplatz® Canine Duct Occluder using a transarterial approach on the following day. No immediate complications were observed other than an acute decrease in left ventricular systolic function. One day after the PDA occlusion transthoracic echocardiography revealed no residual ductal flow, but there was spontaneous echocardiographic contrast in the left ventricle. The patient was discharged with sildenafil, pimobendan, and clopidogrel. Five weeks later when the patient was presented for a recheck examination, the previously documented spontaneous echocardiographic contrast was no longer present. Finding spontaneous echocardiographic contrast in the dog has not previously been reported in association with PDA occlusion.